You are on page 1of 5

Differentiating logarithm and exponential functions

This unit gives details of how logarithmic functions and exponential functions are differentiated from first principles. In order to master the techniques explained here it is vital that you undertake plenty of practice exercises so that they become second nature. After reading this text, and/or viewing the video tutorial on this topic, you should be able to: • differentiate ln x from first principles • differentiate ex

Contents
1. Introduction 2. Differentiation of a function f (x) 3. Differentiation of f (x) = ln x 4. Differentiation of f (x) = ex 2 2 3 4

1

c mathcentre August 27, 2004

B .001)1/0. A.. we have evaluated the expression (1 + t)1/t for a number of decreasing values of t as shown in Table 1.0001 (1 + t)1/t (1 + 1)1/1 (1 + 0. and explore what happens as t reduces further. The derivative. is then given by f ′ (x) = lim δy is the slope of AB . t 1 0. We then δy determine what happens to in the limit as δx tends to zero. f ′ (x).. 2004 2 .705 2. To understand what follows we need to use the result that the exponential constant e is defined as the limit as t tends to zero of (1 + t)1/t i. c mathcentre August 27. and a neighbouring point. (See Figure 1). lim (1 + t)1/t . δx δy f (x + δx) − f (x) = lim δx→0 δx δx→0 δx Use of this result has been explained at some length in the first unit on differentiation from first principles. f (x). which should be revised if necessary.01 (1.1 (1 + 0. Introduction In this unit we explain how to differentiate the functions ln x and ex from first principles.01 0. from first principles we find the slope. Differentiation of a function f (x) δy .1 0. t→0 To get a feel for why this is so.1. You should verify some of the values in the Table.. the value of the expression gets closer to the value of the exponential constant e≈ 2. on the graph of f (x).e.001 (1.0001 = = = = = 2 2.718.01)1/0. Note that as t gets closer to zero. δx Recall that to differentiate any function.594 2.718 We will also make frequent use of the laws of indices and the laws of logarithms. of the δx line joining an arbitrary point.0001)1/0. y f (x + δx) f ( x) B δy f ( x) A x δx x + δx x Figure 1.001 0.1)1/0. 2.717 2.

that the derivative of ln x is equal to 1 .3. x We have 1 1 f ′ (x) = lim ln (1 + t) t t→0 x In this limiting process it is t which tends to zero. We need not worry about x being zero because we are interested in differentiating ln x and the logarithm function is only defined for positive values of x. x 1 1 ln e = x x 1 3 c mathcentre August 27. Because we δx substituted t = we need to let t tend to zero. it can be taken outside the limit to give: f ′ (x) = But we know that t→0 1 1 lim ln (1 + t) t x t→0 lim (1 + t) t = e and so f ′ (x) = since ln e = 1. using the law n log A = log An we can take the inside the logarithm to give t 1 f (x + δx) − f (x) 1 = ln(1 + t) t δx x Then Referring to the general case in Figure 1. To find the derivative we need to let δx tend to zero. from first principles.) 1 f (x + δx) − f (x) = ln(1 + t) δx xt 1 Further. δx = xt. We have shown. So. that is. 2004 . (This In order to simplify what will follow we make a substitution: let t = x substitution is made because in the calculations which follow it is the ratio of δx to x which turns out to be important. this represents the slope of the line joining the two points on the graph of f (x). Differentiation of f (x) = ln x Using the definition of the derivative in the case when f (x) = ln x we find ln(x + δx) − ln x f (x + δx) − f (x) = δx δx A We proceed by using the law of logarithms log A − log B = log to re-write the right-hand side B as firstly 1 1 1 x + δx δx = (ln(x + δx) − ln x) = ln ln 1 + δx δx x δx x δx . and we can regard x as a fixed number.

(This result is obtained using a technique known as the Recall that dx dy dx chain rule. from Section 3. d (ln y ) = 1 dx dy . d 1 Now we know.Key Point if f (x) = ln x then f ′ (x) = 1 x Exercise 1. You should refer to the unit on the chain rule if necessary). Show from first principles. dx d dy d (ln y ) = (ln y ) × . Show from first principles that if f (x) = loga x then f ′ (x) = x ln a 4. Differentiation of f (x) = ex To differentiate y = ex we will rewrite this expression in its alternative form using logarithms: ln y = x Then differentiating both sides with respect to x. that if f (x) = log10 x then 1 f ′ (x) = . 2004 4 . that (ln y ) = and so dy y The idea is now to find 1 dy =1 y dx Rearranging. x ln 10 1 . 2. dy =y dx But y = ex and so we have the important and well-known result that dy = ex dx Key Point if f (x) = ex then f ′ (x) = ex c mathcentre August 27. using exactly the same technique.

5 c mathcentre August 27.The exponential function (and multiples of it) is the only function which is equal to its derivative. that if f (x) = ax then f ′ (x) = ax ln a. using exactly the same technique. 2004 . Exercise 1. Show from first principles.